Potensi Ekstrak Etanol Daun Cnidoscolus aconitifiolus Terhadap Mortalitas Larva Aedes aegypti Instar III - Attiyah Rizki Apriliani; Emantis Rosa; Primasari Pertiwi; Sutyarso (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
Dengue Hemorrhagic Fever (DHF) is a serious global public health problem with a high risk of disease transmission, transmitted by the vector Aedes aegypti. The negative impact of synthetic insecticide use on environmental health and the risk of vector resistance encourage the search for alternative natural larvicides that are safe and environmentally friendly. This study aimed to analyze the efficacy of ethanol extract of Japanese papaya leaves (Cnidoscolus aconitifolius) on the mortality of third instar Aedes aegypti larvae as an effort to control the dengue fever vector. The method used was an experimental study with a Completely Randomized Design (CRD) consisting of seven concentration treatments (0.5%, 1%, 1.5%, 2%, 2.5%, 3%, and control) with four replications. Observations of larval mortality were conducted after 24 hours of exposure. The results of ANOVA analysis showed a highly significant effect (p<0.001) on the mortality of Aedes aegypti larvae. Tukey's HSD further test identified the 3% concentration as the most effective treatment with an average mortality of 85% (17,000). Linear regression analysis showed a strong correlation (R2 = 0.937) with the equation y = 24.643x + 1.785 . These findings prove that the ethanol extract of Japanese papaya leaves has great potential as an effective natural larvicide to support community-based environmental dengue vector control programs.